2019
DOI: 10.7454/jki.v22i1.540
|View full text |Cite
|
Sign up to set email alerts
|

Program Perencanaan Pulang Dapat Meningkatkan Pengetahuan Dan Keterampilan Ibu Yang Melahirkan Bayi Prematur Merawat Bayinya

Abstract: Bayi yang lahir prematur berisiko mengalami permasalahan kesehatan, sehingga membutuhkan perawatan yang intens dari sejak di rumah sakit sampai ketika bayi sudah boleh dipulangkan ke rumah. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh edukasi dalam perencanaan pulang terhadap pengetahuan dan keterampilan ibu merawat bayi prematur. Penelitian ini merupakan studi quasi experiment dengan rancangan pre and post-test without control design. Sampel penelitian ini adalah 35 ibu yang melahirkan bayi pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…Moreover, the mother's formal education level may also affect the mother's knowledge because most respondents have formal with intermediate and high education levels. The level of formal education contributes to determining whether or not a person can easily absorb and understand information obtained through health education (Julianti, Rustina, and Defi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mother's formal education level may also affect the mother's knowledge because most respondents have formal with intermediate and high education levels. The level of formal education contributes to determining whether or not a person can easily absorb and understand information obtained through health education (Julianti, Rustina, and Defi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of educational programs during discharge planning which is carried out for three days can increase the knowledge and skills of mothers caring for premature babies, this is evidenced by the results of research which show that there is a significant difference between the average score of knowledge of mothers caring for premature babies, scores of breastfeeding skills, and kangaroo method care skills scores (PMK) before and after being given education during discharge planning with a p value of 0.001 (Julianti, Rustina & Defi, 2019). Another study showed that 86.4% of respondents experienced a decrease in anxiety and 18.2% of respondents expe-rienced an increase in self-efficacy after being given an education.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this breastfeeding positions should be discussed with mothers in the discharge planning program as Julianti, Rustina and Efendi confirmed this topic influences the knowledge and skill of mothers who are ready to be discharged. 23 …”
Section: Discussionmentioning
confidence: 99%